P594 'Two's company'. Transitioning from one to two on-call registrars in an Irish Paediatric tertiary hospital, the non-consultant hospital doctor's perspective. (June 2019) - Fitzgerald, Michael; Forman, Eva; McCarron, Laura; Foran, Adrienne
Abstract : Introduction: This study was conducted in a 154 bed Tertiary Paediatric Hospital where the medical on-call NCHD (Non-Consultant Hospital Doctor) team of one Registrar and one SHO both a 25 hour shift. NCHDs had expressed their concerns regarding their workload and fatigue levels on-call, coupled with a significant number coming off the on call rota due to stress and fatigue. Aims: This study aims to assess the impact of introducing a second registrar to the on-call team had on NCHD experience of on-call work. Methodology: NCHDs working the Paediatric medical on-call rota were invited to complete an online survey exploring their experiences of being on-call. These results were discussed with the hospital directorate and a second registrar was introduced into the 25hour on-call team. Three months following the introduction of the second registrar the same survey was repeated. Results: 18 NCHDs (8 Registrars, 10 SHOs) took part in the initial survey and 16 NCHDs (10 Registrars, 6 SHOs) took part follow up survey. Prior to the introduction of the second registrar, 66% and 33% of NCHDs reported getting less than 1 hour and between 1–3 hours of uninterrupted rest on call respective. Following the introduction of the second registrar, 6% reported less than one hour, 44% reported 1–3 hrs and 50% reported 3–5 hrs of uninterrupted rest on call. In the initial survey one participant (5%) reported having adequate time to eat on call, this figure rose to 63% (10 participants) following the introduction of the second registrar. In the initial survey all participants reported fatigue levels as unmanageable or overwhelming by the end of their 25 hour shift. Following the introduction of the second registrar 50% of participants reported manageable fatigue levels by the end of their shift, the remaining 50% reported fatigue levels as unmanageable or overwhelming. Discussion: The introduction of a second registrar on call resulted in marked improvement in the on-call experience of the participants, there was an improvement in uninterrupted rest and lower levels of reported fatiuge. Despite the presence of a second registrar 50% of participants still reported fatigue levels as unmanageable or overwhelming by the end of their shift. Conclusion: Paediatrics is recognised as a satisfying speciality albeit a difficult one with a high workload and a high rate of attrition and burnout. Interventions such as addition staff on-call may protect junior staff from burnout and result in higher staff retention in the speciality.